Research Of The Process Of Storage Of Soybean Based On System Thınkıng - Tursunova Nargiza Nigmatovna.,Bahriddinova Nasiba Murodovna., Zaripova Mohira Juraevna., Murodova Istat Nurillaevna (International Journal of Advanced Science and Technology, 2020)
search for alternative ways of growing crops and applying innovative developments to increase the production of high-quality crop products is an acute issue. Decisions of the Government of the Republic of Uzbekistan are aimed at the development of agriculture, including vegetable growing, animal husbandry. Today, in agriculture, one of the main problems remains the increase and stabilization of soybean cultivation, since soy products are the main source of environmentally friendly protein balanced in amino acid composition. The scientific article describes the main factors affecting the quality storage of soybean seeds based on the analysis. Also described are methods for storing soybean grain, the advantages of a method for storing soybean seeds using plastic bags, the influence of the main factor in the storage of soybean seeds moisture. The main reason for the decline in soybean quality during storage is justified - the development of mushrooms. The conditions for the safe storage of soybean seeds, the basic requirements for the quality storage of soybean in production, a set of measures to preserve the quality of the soybean crop at different storage periods are given.